DNA barcoding facilitates discovery and description of two new species of the Mystacides azureus Species Group (Trichoptera: Leptoceridae) in Japan - Kuhara, Naotoshi; Nozaki, Takao; Zhang, Ao; Zhou, Xin (Zootaxa, 2023)
We examined adult specimens of the Mystacides azureus Species Group (Trichoptera: Leptoceridae) collected in Japan and confirm three species including M. azureus Linnaeus 1761 and two new species, M. rivularis and M. moritai. Males and females of the new species are described. Mystacides azureus in Japan is shown to have a considerable variation in morphology of the male tergum X. We analyzed mitochondrial COI barcodes of the genus Mystacides including these three species to confirm their species status. A maximum likelihood phylogeny based on COI barcodes shows monophyly of the new species. It also supports the hypothesis that morphological variation of the male tergum X in Japanese populations is intraspecific in only M. azureus.